Implementation of the STAD Type Cooperative Learning Model to Improve Students' Motivation and Civics Learning Outcomes - Sepriandison Saragih (Jurnal Basicedu, 2021)
This study aims to increase the motivation and learning outcomes of Civics in class X-4 SMA Negeri 3 Pematangsiantar by applying the STAD type cooperative learning model. This research is a classroom action research conducted at SMA Negeri 3 Pematangsiantar, the subjects of this research are students of class X-4 with a total of 30 students. The results showed that student learning outcomes at the basic score of the average value of 48.61 increased by 16.95 points to 65.56 in the first cycle. In the second cycle the average score was 71.67 increase from the first cycle of 6.11 points. Classical completeness on a base score of 33% (13 students). In the first cycle test, the completeness increased to 72.5% (19 students). In the second cycle, classical completeness increased to 87.5% (25 students). From the results of the study, it can be concluded that the application of the cooperative learning model of the student teams achievement division (STAD) type can increase the motivation and learning outcomes of Civics in class X-4 SMA Negeri 3 Pematangsiantar